Is back pain affecting you? Practical advice on back pain self prevention for the nurses and physiotherapists - Spannbauer, Anna; Danek, Joanna (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2008)
Chronic back pain is the most common health problem in modern society. Nurses and physiotherapists taking care of patients each day are also affected by this illness. There are many causes of back pain. The most important are: lifting and transferring of patients, incorrect sitting position, and a lack of proper physical activity. The correct technique of patient transfer may decrease the risk of spinal strain. Prophylactic activities such as stretching exercises, strengthening exercises, and loosening-up exercises of the proper muscle groups, known as the “back pain prevention school”, are also very important. Often recommended physical activities such as swimming, walking, dancing and aerobics are the basis of physical and mental well-being.